Employment protection and innovation intensity - Gavin Murphy; Iulia Siedschlag; John McQuinn (The Economic and Social Research Institute (ESRI), 2012)
We examine the impact of the strictness of employment protection legislation on innovation intensity. To this purpose, we use a panel of annual data from OECD countries over the period 1990-1999 and estimate difference-in-difference models to explain the variation of innovation intensity between industries within countries. Our estimates indicate that stricter employment protection legislation led to significantly lower innovation intensity in industries with higher job reallocation rates or higher layoff propensities. Further, we find that the strictness of employment regulations on the use of temporary contracts had a stronger impact on innovation intensity than the strictness of employment protection for regular contracts. Our findings are robust to additional industry covariates and to other labour market institutions that may affect innovation performance and industry job reallocation propensity. In addition, our sensitivity analysis indicates that our results are not driven by the particular measures of employment protection legislation and industry layoff propensity that we use or by any country in our sample.
Keywords: F43; O31; O43; 330; Employment Protection; Innovation; Industry Specialisation